Características agro-socio-ambientales de la agricultura familiar productora de granos andinos en la comunidad de Ninin Cachipata de la provincia de Cotopaxi - Nacimba Cazares, María José (2018)
The purpose of the research was to determine the agro-socio-environmental characteristics of the family agriculture producing Andean grains of the Ninin Cachipata community, Cochapamba parish, of Cotopaxi province. In order to know these characteristics, information was collected through a survey of the practices carried out by the farmers, in the same way, primary information was generated on the climate perception and its influence on the crops, using the methodology of focal groups, and was compared with statistics from the Instituto Nacional de Meteorología e Hidrología (INAMHI). With the data obtained, climatic factors such as frost and drought affect 100% of the crops in the study area. In the socioeconomic aspect, the main source of income for the community is agriculture; the same one that presents a reduction of the system because 50% of the population migrates. In the analysis of the resources for the production, it was identified that the soil in the sector is of the sandy-sandy textural class, with little fertility; in terms of production systems, it was verified that 50% of producers perform crop rotation, and 6% polyculture, and 44% monoculture, especially in chocho Lupinus mutabilis, this practice has caused ecological vulnerability and affects the appearance of pests and diseases, and their subsequent use of pesticides, which has generated unsustainability of the productive system of Andean grains in the community.